2022
DOI: 10.7150/thno.69999
|View full text |Cite
|
Sign up to set email alerts
|

Advanced nanocarrier- and microneedle-based transdermal drug delivery strategies for skin diseases treatment

Abstract: Skin diseases are the fourth leading cause of nonfatal and chronic skin diseases, acting as a global burden and affecting the world economy. Skin diseases severely impact the patients' quality of life and have influenced their physical and mental state. Treatment of these skin disorders with conventional methods shows a lack of therapeutic efficacy, long treatment duration, recurrence of the condition, and systemic side effects due to improper drug delivery. However, these pitfalls can be overcome with the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 189 publications
(207 reference statements)
0
65
0
Order By: Relevance
“…In addition, when treated with high concentrations of PAMAM-NH 2 dendrimers, PCNA was highly expressed in all layers of the skin, and the nuclear immune response was enhanced, thus indicating a cell proliferation disorder. Collectively, microscopic evaluations and immunohistochemical analyses showed that cationic PAMAM dendrimers readily led to significant skin toxicity and that low concentrations should be considered for practical external use [118,133].…”
Section: Skin Toxicitymentioning
confidence: 99%
“…In addition, when treated with high concentrations of PAMAM-NH 2 dendrimers, PCNA was highly expressed in all layers of the skin, and the nuclear immune response was enhanced, thus indicating a cell proliferation disorder. Collectively, microscopic evaluations and immunohistochemical analyses showed that cationic PAMAM dendrimers readily led to significant skin toxicity and that low concentrations should be considered for practical external use [118,133].…”
Section: Skin Toxicitymentioning
confidence: 99%
“…This treatment technique has gained enormous attention from researchers owing to its various benefits, i.e., it avoids the degradation of therapeutics in the gastrointestinal tract, circumvents the first-pass metabolism in the liver (in the case of oral delivery), and prevents the invasive and painful approach via the intravenous delivery of drugs (Figure 3) (Fernando et al, 2018;Qu et al, 2022); hence, it is considered an effective approach in transdermal drug delivery. Microneedles are composed of an array of micron-sized needles that pierce the SC (10-20 um) and deliver the actives directly to the viable epidermis, bypassing the SC barrier and providing high drug bioavailability compared to Frontiers in Drug Delivery frontiersin.org creams and the transdermal patch (Figure 1) (Waghule et al, 2019;Avcil and Çelik, 2021;Ali et al, 2022;Qu et al, 2022). Due to these various advantages, microneedles and their patches have also been translated to clinical stages in the delivery of vaccines (Fernando et al, 2018); however, this strategy has some limitations, such as compatibility, loading capacity, dose restriction due to small size of microneedles, irritation, and inflammatory immune response (Avcil and Çelik, 2021).…”
Section: Microneedlesmentioning
confidence: 99%
“…Transdermal drug delivery approaches can avoid first-pass metabolism, control the drug release rates over a prolonged time, and reduce the risk of systemic side effects ( Morry et al, 2015 ). Skin also acts as a reservoir, which enables the diffusion of the penetrated drugs from skin continuously for a longer period and presents an opportunity of lower frequency of administration ( Qu et al, 2022 ). As the stratum corneum (SC) layer of the skin is the capital barrier which limits the penetration of most drugs, many approaches have been adopted to disrupt the SC layer and increase skin permeability, including physical enhancers (iontophoresis, electroporation, sonophoresis, and microneedles), chemical enhancers (alcohol and peptide), and delivery vehicles (spherical nucleic acid and lipoplexes) ( Ita 2017 ; Phatale et al, 2022 ; Qu et al, 2022 ).…”
Section: Transdermal Drug Delivery Systemsmentioning
confidence: 99%
“…Skin also acts as a reservoir, which enables the diffusion of the penetrated drugs from skin continuously for a longer period and presents an opportunity of lower frequency of administration ( Qu et al, 2022 ). As the stratum corneum (SC) layer of the skin is the capital barrier which limits the penetration of most drugs, many approaches have been adopted to disrupt the SC layer and increase skin permeability, including physical enhancers (iontophoresis, electroporation, sonophoresis, and microneedles), chemical enhancers (alcohol and peptide), and delivery vehicles (spherical nucleic acid and lipoplexes) ( Ita 2017 ; Phatale et al, 2022 ; Qu et al, 2022 ). It is reported that transdermal drug delivery approaches enable topical drug delivery to the periarticular tissues of TMJs, which offer a painless and convenient platform to treat TMJOA-associated conditions ( Figure 2 and Table 2 ).…”
Section: Transdermal Drug Delivery Systemsmentioning
confidence: 99%